Clinical Holistic Medicine (Mindful, Short-Term Psychodynamic Psychotherapy Complemented with Bodywork) in the Treatment of Experienced Impaired Sexual Functioning - Søren Ventegodt; Suzette Thegler; Tove Andreasen; Flemming Struve; Lars Enevoldsen; Laila Bassaine; Margrethe Torp; Joav Merrick (The Scientific World Journal)
In this clinical follow-up study, we examined the effect of clinical holistic medicine (psychodynamic short-term therapy complemented with bodywork) on patients with poor self-assessed sexual functioning and found that this problem could be solved in 41.67% of the patients ((95% CI: 27.6156.7%; 1.75 < NNT < 3.62, p = 0.05). The bodywork was inspired by the Marion Rosen method and helped the patients to confront painful emotions from childhood trauma(s), and thus accelerated and deepened the therapy. The goal of therapy was the healing of the whole life of the patient through Antonovsky-salutogenesis. In this process, rehabilitation of the character and purpose of life of the patient was essential, and assisted the patient to recover his or her sense of coherence (existential coherence). We conclude that clinical holistic medicine is the treatment of choice if the patient is ready to explore and assume responsibility for his or her existence (true self), and willing to struggle emotionally in the therapy to reach this important goal. When the patient heals existentially, quality of life, health, and ability to function in general are improved at the same time. The therapy was mindful in its focus on existential and spiritual issues. The patients received in average 14.8 sessions at the cost of 1,188 EURO.